Upaya Peningkatan Konsep Diri Positif Peserta Didik Kelas Xii Sma Nahdlatul Ulama 1 Gresik Melalui Forgiveness Therapy - Riza, Muhammad Badril (Jurnal Mahasiswa Manajemen, 2020)
Abstract Background - There are indications of low positive self-concept, especially in class XII students. Often the negative self-concept experienced by students is more influenced by unfinished emotion, namely feelings of being wronged in the past by the surrounding environment that has not been resolved so as to form various consequences of unconscious behavior in the present. Objective - Describe the application of classical forgiveness therapy guidance services in improving the positive self-concept of class XII students of SMA Nahdlatul Ulama 1 Gresik. Design / methodology / approach - action research guidance and counseling (PTBK). Findings - Improvements in classical guidance services from cycle 1 to cycle 2 have succeeded in increasing the positive self-concept of students as evidenced by the decline in students in the low and very low categories on the results of the self-concept questionnaire. Research implications - This study provides contributions in the management of students' self-concepts. Research limitations - This research on guidance and counseling was carried out with due regard to pandemic conditions during the study. So that service settings are also limited by space (keep distance) and time. For further researchers, this can be done more optimally through different service designs under normal conditions.